Criminology and Authority - Dobryninas, Aleksandras (Sociologija. Mintis ir veiksmas, 2007)
Introduction: The text introduces an issue of journal Sociologija. Mintis ir veiksmas, which contains a number of papers presented in the Baltic Criminological Conference in 2006.